(untitled) (Research, Society and Development, 2022)
Community seed banks play a key role in the preservation of native seeds and food security. The relevance of native seeds is not only limited to the issue of preservation of plant species, but also reverberates on social, cultural, ecological, and economic conditions. This literature review aimed to evaluate publications in the form of scientific articles, abstracts, and dissertations about community seed banks. Topics such as native seeds, community seed banks, adaptation and resistance of native seeds to the conditions of the semi-arid region, importance of native seeds to the semi-arid region, production, multiplication and storage of native seeds, physical and/or physiological quality of native seeds were addressed in publications from different databases (Google Scholar, Periódicos CAPES, Scielo, and Web of Science). After the data collection step, the scientific articles, abstracts, and dissertations were read, where the most relevant information about the topic was obtained, such as year of publication, publication database, topics addressed, and languages. For the themes addressed, a total of 28,737 publications were found in the period 2011 to 2021 in the form of articles, abstracts and dissertations, and the platform with the greatest prominence was Google Scholar. However, despite the large collection found, these are still insufficient due to the importance of the theme, especially in relation to the advent of climate change, it is essential the knowledge, preservation and multiplication of native seeds in the Brazilian semiarid region.